INTRA-ABDOMINAL INFECTION AND ACUTE ABDOMEN-EPIDEMIOLOGY, DIAGNOSIS AND GENERAL PRINCIPLES OF SURGICAL MANAGEMENT - Jovanović Dušan; Lončar Zlatibor; Doklestić Krstina; Karamarković Aleksandar (Sanamed, 2015)
Intra-abdominal infections are multifactorial and present an complex inflammatory response of the peritoneum to microorganisms followed by exudation in the abdominal cavity and systemic response Despite advances in management and critical care of patients with acute generalized peritonitis due to hollow viscus perforation, prognosis is still very poor, with high mortality rate. Early detection and adequate treatment is essential to minimize complications in the patient with acute abdomen. Prognostic evaluation of complicated IAI by modern scoring systems is important to assess the severity and the prognosis of the disease. Control of the septic source can be achieved either by nonoperative or operative means. Nonoperative interventional procedures include percutaneous drainages of abscesses. The management of primary peritonitis is non-surgical and antibiotic- treatment. The management of secondary peritonitis include surgery to control the source of infection, removal of toxins, bacteria, and necrotic tissue, antibiotic therapy, supportive therapy and nutrition. "Source control" is sine qua non of success and adequate surgical procedure involves closure or resection of any openings into the gastrointestinal tract, resection of inflamed tissue and drainage of all abdominal and pelivic collections.